PENARIKAN HARTA HIBAH OLEH ORANG TUA TERHADAP ANAKNYA - Azwar Hamid (JURIS (Jurnal Ilmiah Syariah), 2017)
Considering the love and affection of parents that have been given to their children, it can be humanly judged that if the parents take back (ruju’) the property that they have granted to their children, then this withdrawal may be justified. However, when speaking of Islamic laws, what are the regulations found in Islamic law concerning with ruju’? Is it legally permitted? Dealing with this issue, Islamic scholars have different opinions. This research was library research with descriptive analysis. After analyzing the opinions of Imam Syafi'i and Imam Abu Hanifah dealing with ruju’ which were suppoted with  the reason of the two scholars, it can be concluded that the opinions of the two scholars can be used and carried out in accordance with the regulations that allow and forbid to withdraw the grant property.